Penerapan teknik self regulation learning untuk meningkatkan kedisiplinan belajar siswa - Firdayanti Nur Ramadhani; Nurhidayatullah D; Abdul Wahid (Universitas Indraprasta PGRI, 2022)
the objectives of this study are: a) to describe the learning discipline ability of students at SMP Negeri 23 Makassar before and after being given self-regulation learning techniques, and b) to find out whether the application of self-regulation learning techniques can improve the learning discipline abilities of students in SMP Negeri 23 Makassar. The approach used is a quantitative experiment with a pre-experimental design. The subjects of this study were 10 people who were class VIII students at SMP Negeri 23 Makassar. Data collection using a questionnaire instrument. Data analysis used descriptive statistical analysis with Wilcoxon test. The results showed that: a) the level of learning discipline ability of students at SMP Negeri 23 Makassar before being given self-regulation learning techniques was in the low category and after giving self-regulation learning techniques was in the high category, and b) self-regulation learning techniques could improve their abilities. learning discipline in students at SMP Negeri 23 Makassar.